Surfaces of a Constant Negative Curvature - G. M. Gharib (International Journal of Differential Equations)
I study the geometric notion of a differential system describing surfaces of a constant negative curvature and describe a family of pseudospherical surfaces for the nonlinear partial differential equations with constant Gaussian curvature .